A hyperactive mutant of interferon‐regulatory factor 4. Issue 5 (30th September 2018) - Kang, Chol Ho; Hartmann, Enno; Menke, Lisa; Staudenraus, Daniel; Abass, El‐Fadil; Raifer, Hartmann; Porapu, Alekya; Camara, Bärbel; Brüstle, Anne; Pinkenburg, Olaf; Bieringer, Maria; Lohoff, Michael
Abstract : We found that deletion of the final 30 amino acids of transcription factor IRF4's (interferon‐regulatory factor) C‐terminus creates hyperactive IRF4. When introduced into IRF4‐deficient CD4 + or CD8 + T cells, more type 17 differentiation was found compared to WT IRF4. Interestingly, Th9 differentiation and Th2‐linked IL‐13 production were much less altered.